Evaluation of Antioxidant Activity of Branch Extract from Pouteria campechiana (Sawo Walanda) - Batari, Nirmala Puteri; Setyo Purnomo, Adi; Seviani, Winda (KOVALEN: Jurnal Riset Kimia, 2025)
The objective of this research was to assess the antioxidant activity of branch extract (Pouteria campechiana) through analysis of bioactive compound content and antioxidant activity. The sample was extracted through maceration, utilizing methanol as the solvent which produced a yield of 6.03 %. The quantity of phenolic constituents in the extract was determined using the Folin-Ciocalteu method, with gallic acid as the standard, yielding a result of 195.22 mg GAE/g extract. The quantity of flavonoid constituents was determined using gallic acid as a standard resulting in a value of 830.5 mg QE/g extract. Antioxidant activity was tested using two methods, namely DPPH and ABTS. The results of the DPPH test showed an inhibition percentage of 91% with an IC50 value of 3,322 ppm, while the ABTS test showed an inhibition of 99% with an IC50 of 2,206 ppm at a concentration of 10,000 ppm. Based on these results, the Pouteria campechiana branch extract has very weak antioxidant activity, suggests a limited potential as natural bioactive compound source.